The 2020 Royal Australian and New Zealand College of psychiatrists clinical practice guidelines for mood disorders: Bipolar disorder summary. (27th December 2020) - Malhi, Gin S.; Bell, Erica; Boyce, Philip; Bassett, Darryl; Berk, Michael; Bryant, Richard; Gitlin, Michael; Hamilton, Amber; Hazell, Philip; Hopwood, Malcolm; Lyndon, Bill; McIntyre, Roger S.; et al.
Abstract: Objectives: To provide a succinct, clinically useful summary of the management of bipolar disorder, based on the 2020 Royal Australian and New Zealand College of Psychiatrists clinical practice guidelines for mood disorders (MDcpg 2020 ). Methods: To develop the MDcpg 2020, the mood disorders committee conducted an extensive review of the available literature to develop evidence‐based recommendations (EBR) based on National Health and Medical Research Council (NHMRC) guidelines. In the MDcpg 2020, these recommendations sit alongside consensus‐based recommendations (CBR) that were derived from extensive deliberations of the mood disorders committee, drawing on their expertise and clinical experience. This guideline summary is an abridged version that focuses on bipolar disorder. In collaboration with international experts in the field, it synthesises the key recommendations made in relation to the diagnosis and management of bipolar disorder. Results: The bipolar disorder summary provides a systematic approach to diagnosis, and a logical clinical framework for management. It addresses the acute phases of bipolar disorder (mania, depression and mixed states) and its longer‐term management (maintenance and prophylaxis). For each phase it begins with Actions, which include important strategies that should be implemented from the outset wherever possible. These include for example, lifestyle changes, psychoeducation and psychological interventions. In each phase, the summary advocates the use of Choice medications for pharmacotherapy, which are then used in combinations along with additional Alternatives to manage acute symptoms or maintain mood stability and provide prophylaxis. The summary also recommends the use of electroconvulsive therapy (ECT) for each of the acute phases but not for maintenance therapy. Finally, it briefly considers bipolar disorder in children and its overlap in adults with borderline personality disorder. Conclusions: The bipolar disorder summary provides up to date guidance regarding the management of bipolar disorder, as set out in the MDcpg 2020 . The recommendations are informed by evidence and clinical expertise and experience. The summary is intended for use by psychiatrists, psychologists and primary care physicians but will be of interest to anyone involved in the management of patients with bipolar disorder.